Twenty Years on: Reflections on the CEDISYS Project. Combining True Concurrency with Process Algebra. - HENNESSY, MATTHEW (Springer, 2008)
We recall some memories of the Esprit Basic Research Action CEDISYS, a small, well-focussed and fruitful project which brought together researchers at the meeting point of true concurrency and process algebra, in the period 1988-1991. The project was initiated and effectively animated by Ugo Montanari, a passionate and long-time advocate of both these approaches to the semantics of concurrency.
PUBLISHED
Keywords: Computer science; Mathematics